Influence Profitability and Firm Value on Corporate Social Responsibility in the Sector Registered Consumer Goods Industry on the Indonesia Stock Exchange - Monalisa (Pustaka Digital Indonesia, 2021)
This study aims to determine the effect of Profitability as measured by Return On Assets (ROA) and Firm Value as measured by Tobin's Q on Corporate Social Responsibility. The population in this study is the consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period as many as 54 companies and the number of samples used in this study were 11 companies which were taken based on purposive sampling technique . The type of research used in this research is quantitative. The data analysis technique used in this research is descriptive analysis and multiple linear regression analysis. Data obtained by using statistical calculations through SPSS 23.0 The results of this study indicate that Profitability as measured by Return On Assets (ROA) does not have a significant effect on Corporate Social Responsibility and Firm Value as measured by Tobin's Q does not have a significant effect on Responsibility. Corporate Social.